ATMOSPHERIC OZONE PROFILES DURING VASYLKIV OIL BURNING EPISODE - Shavrina, A.; Veles, A.; Milinevsky, G.; Grytsai, A.; Liptuga, A.; Romanyuk, Ya. (Одеські астрономічні публікації, 2016)
Ground-based Fourier Transform Infrared spectrometer (FTIR) observations have been used for study stratosphere/troposphere ozone vertical distribution during Vasylkiv (near Kyiv, Ukraine) incident of petroleum storage burning in June 8–14, 2015.